Integrated stratigraphic framework of the Upper Assam Basin, northeast India: tectonic evolution, sequence stratigraphy and future research directions - M. Gogoi; D. Bhuyan; D. Majumdar (Australian Journal of Earth Sciences, 2026)

NPF-induced CCN enhancement over an urban location in Eastern Himalayan Foothills: A campaign-based study - Barlin Das; Binita Pathak; Uday Bhattacharjee; Partha Jyoti Sahu; Arundhati Kundu; Arup Borgohain; Mukunda M. Gogoi; Shyam S. Kundu; Kalyan Bhuyan; Pradip K. Bhuyan (Atmospheric Environment, 2025)

Attention-guided deep framework for polyp localization and subsequent classification via polyp local and Siamese feature fusion - Pradipta Sasmal; Susant Kumar Panigrahi; Swarna Laxmi Panda; M. K. Bhuyan (Medical & Biological Engineering & Computing, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Integrated use of field sensors, PhenoCam, and satellite data for pheno-phase monitoring in a tropical deciduous forest of Dalma Wildlife Sanctuary, Jharkhand, India: initial results from the Indian Phenology Network - C. Jeganathan; Beependra Singh; C. P. Singh; M. D. Behera; Sanjay Srivastava; S. R. Natesha; Kulwant Singh; Rajiv Ranjan; Maun Prakash; Abhishek Kumar; M. R. Pandya; B. K. Bhattacharya; et al. (Biodiversity and Conservation, 2024)

Thermal adaptability of neonatal piglets: Early life welfare crisis - Kalyan De; Nitin M. Attupuram; Salam Jayachitra Devi; Souvik Paul; Gagan Bhuyan; Vivek Kumar Gupta (Journal of Veterinary Behavior, 2024)

Adsorption of methylene blue by composite foams containing alkali-activated blast furnace slag and lignin - M. A. H. Bhuyan; T. Luukkonen (International Journal of Environmental Science and Technology, 2024)
Adsorption is a promising method to remove dyes, such as methylene blue, from wastewater. In this study, a dynamic adsorption set-up was used to treat synthetic wastewater containing methylene blue by using alkali-activated blast furnace slag and lignin composite foam. The structure of the foam without lignin was first optimized by comparing cationic and non-ionic surfactants in the preparation of the foam via the direct foaming method. The selection of the surfactant affects the porosity and pore structure of the foam through different abilities to stabilize the gas–liquid interface and changes in the viscosity of the fresh-state paste. The foam prepared with non-ionic Triton X-114 surfactant had the highest adsorption performance and was selected for the optimization of adsorption conditions. The optimized conditions were 5 mg/L influent concentration of methylene blue, pH of 7, and flow rate of 1.0 L/h (corresponding to ~ 9 min empty bed contact time). To further enhance the methylene blue adsorption performance, a composite containing lignin was prepared. The optimum lignin amount in the foam was 0.8 wt% and it resulted a ~ 93% higher adsorption amount compared to the foam without lignin. The highest cumulative adsorption capacity in this dynamic adsorption setup was 39.5 mg/g, which is among the highest reported values for methylene blue removal by monolithic adsorbents. The present study provides a proof of concept for the enhancement of adsorption performance of alkali-activated materials by introduction of lignin into the structure.

The differential conjugate hemisphere ionospheric response during solstice storms and the winter side maxima - Bitap Raj Kalita; P.K. Bhuyan; M. Choudhary; D. Chakrabarty; R.C. Tiwari; M. Le. Huy; K. Wang; K. Hozumi; T. Komolmis; S.J. Nath (Advances in Space Research, 2024)

Observations on the decadal variability of aerosol in eastern Himalayan foothills: Evidence of an anthropologically induced positive shift - Tamanna Subba; Binita Pathak; Mukunda M. Gogoi; P. Ajay; Papori Dahutia; Aniket Chakraborty; Pradip K. Bhuyan (Atmospheric Environment, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Anatomical, physiological, and chemical alterations in lichen (Parmotrema tinctorum (Nyl.) Hale) transplants due to air pollution in two cities of Brahmaputra Valley, India - Rebecca Daimari; Pranamika Bhuyan; Sharfaa Hussain; Sanjeeva Nayaka; M. A. Jafar Mazumder; Raza R. Hoque (Environmental Monitoring and Assessment, 2021)

Tebuconazole and trifloxystrobin regulate the physiology, antioxidant defense and methylglyoxal detoxification systems in conferring salt stress tolerance in Triticum aestivum L. - Sayed Mohammad Mohsin; Mirza Hasanuzzaman; Kamrun Nahar; Md. Shahadat Hossain; M. H. M. Borhannuddin Bhuyan; Khursheda Parvin; Masayuki Fujita (Physiology and Molecular Biology of Plants, 2020)

Biomonitoring by epiphytic lichen species—Pyxine cocoes (Sw.) Nyl.: understanding characteristics of trace metal in ambient air of different landuses in mid-Brahmaputra Valley - Rebecca Daimari; Pranamika Bhuyan; Sharfaa Hussain; Sanjeeva Nayaka; M. A. Jafar Mazumder; Raza Rafiqul Hoque (Environmental Monitoring and Assessment, 2020)

Dynamics of morpho-physiological characteristics of Cassia tora L. (Fabaceae) in oil field pollution stress environment - B. Sarma; S. K. Chanda; P. R. Bhattacharyya; M. Bhuyan (International Journal of Environmental Science and Technology, 2019)

Explicating physiological and biochemical responses of wheat cultivars under acidity stress: insight into the antioxidant defense and glyoxalase systems - M. H. M. Borhannuddin Bhuyan; Mirza Hasanuzzaman; Jubayer Al Mahmud; Md. Shahadat Hossain; Mazhar Ul Alam; Masayuki Fujita (Physiology and Molecular Biology of Plants, 2019)

Silicon-induced antioxidant defense and methylglyoxal detoxification works coordinately in alleviating nickel toxicity in Oryza sativa L. - Mirza Hasanuzzaman; Md. Mahabub Alam; Kamrun Nahar; Sayed Mohammad Mohsin; M. H. M. Borhannuddin Bhuyan; Khursheda Parvin; Barbara Hawrylak-Nowak; Masayuki Fujita (Ecotoxicology, 2019)

Acetate-induced modulation of ascorbate: glutathione cycle and restriction of sodium accumulation in shoot confer salt tolerance in Lens culinaris Medik. - Md. Shahadat Hossain; Mirza Hasanuzzaman; Md. Mahmodul Hasan Sohag; M. H. M. Borhannuddin Bhuyan; Masayuki Fujita (Physiology and Molecular Biology of Plants, 2019)

Mobile Health Application and e-Health Literacy: Opportunities and Concerns for Cancer Patients and Caregivers - Hyunmin Kim; Joy V. Goldsmith; Soham Sengupta; Asos Mahmood; M. Paige Powell; Jay Bhatt; Cyril F. Chang; Soumitra S. Bhuyan (Journal of Cancer Education, 2019)

Genetic deficiency of the tumor suppressor protein p53 influences erythrocyte survival - Rosi Bissinger; Elisabeth Lang; Irene Gonzalez-Menendez; Leticia Quintanilla-Martinez; Mehrdad Ghashghaeinia; Lisann Pelzl; Basma Sukkar; Abdulla Al Mamun Bhuyan; Madhuri S. Salker; Yogesh Singh; Birgit Fehrenbacher; Hajar Fakhri; et al. (Apoptosis, 2018)

Impact of seasonal thermal stress on physiological and blood biochemical parameters in pigs under different dietary energy levels - P. K. Pathak; R. Roychoudhury; J. Saharia; M. C. Borah; D. J. Dutta; R. Bhuyan; D. Kalita (Tropical Animal Health and Production, 2018)

Nitric oxide-induced salt stress tolerance in plants: ROS metabolism, signaling, and molecular interactions - Mirza Hasanuzzaman; Hirosuke Oku; Kamrun Nahar; M. H. M. Borhannuddin Bhuyan; Jubayer Al Mahmud; Frantisek Baluska; Masayuki Fujita (Plant Biotechnology Reports, 2018)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)
In order to understand the climatic implications of atmospheric aerosols, top of atmosphere ( TOA ) shortwave ( SW , 0.3–5 µm) fluxes and aerosol optical depth ( AOD ) at 550 nm retrieved simultaneously by clouds and the earth's radiant energy system ( CERES ) and moderate resolution imaging spectroradiometer ( MODIS ) instruments, respectively, are analysed over North‐East India and its adjoining areas for the period July 2002–December 2013. The aerosol‐free TOA flux obtained by establishing the linear regression between CERES SW TOA fluxes and MODIS AODs exhibits strong seasonality with peak values in monsoon and minimum in winter. Same seasonality is captured by the Santa Barbara DISORT Atmospheric Radiative Transfer ( SBDART ) model, but with difference in absolute values. SBDART code is used to extend instantaneous radiative forcing estimates into 24‐h averages. AOD over the North East India region with complex terrain shows altitudinal variation with maximum value at the lowest elevation site Dhaka and minimum value at the high‐altitude locations Shillong and Aizwal. In general, strong seasonality in AOD is observed with a peak in pre‐monsoon (March–May) and dip in post‐monsoon (October–November) at all the locations. The direct instantaneous TOA shortwave aerosol radiative forcing ( SWARF ) shows maximum values in pre‐monsoon over all the locations except at Guwahati, Banmauk, Aizawl, and Shillong. The lowest value of instantaneous SWARF is observed in post‐monsoon except at Banmauk and Shillong. Climatologically TOA diurnally averaged SWARF varies between −6.95 W m −2 in Aizawl to −20.39 W m −2 in Shillong. In general, the TOA SW forcing efficiency is highest in monsoon at all the locations. The radiative forcing efficiency is found to be less negative when surface reflectance increases.

Flood Hydrograph with Synthetic Unit Hydrograph Routing - M. K. Bhuyan; Sanjay Kumar; Joygopal Jena; P. K. Bhunya (Water Resources Management, 2015)

Spatial heterogeneity in near surface aerosol characteristics across the Brahmaputra valley - Binita Pathak; Arup Borgohain; Pradip Kumar Bhuyan; Shyam Sundar Kundu; S Sudhakar; Mukunda M Gogoi; Toshihiko Takemura (Journal of Earth System Science, 2014)

Understanding Darjeeling tea flavour on a molecular basis - Bornali Gohain; Sangeeta Borchetia; Priyadarshini Bhorali; Niraj Agarwal; L. P. Bhuyan; A. Rahman; K. Sakata; M. Mizutani; B. Shimizu; G. Gurusubramaniam; R. Ravindranath; M. C. Kalita; et al. (Plant Molecular Biology, 2012)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Oviposition behaviour of the rice hispa Dicladispa armigera (Coleoptera: Chrysomelidae) - L.K. Hazarika; M. Deka; M. Bhuyan (International Journal of Tropical Insect Science, 2005)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)